Alexander Nevsky [videorecording (DVD)] - Eisenstein, Sergei, 1898-1948; Vasilʹev, D. (Dmitriĭ); Cherkasov, Nikolaĭ Konstantinovich, 1903-1966; Okhlopkov, N. P. (Nikolaĭ Pavlovich); Abrikosov, Andreĭ Lʹvovich, 1906-1973 (Corinth Video ; Distributed exclusively by Image Entertainment, 1998)
Biographical story of Prince Alexander Nevsky and his successful resistance against an attempt by the Teutonic Knights to invade Russia in 1242.